2021
DOI: 10.1007/s00604-021-05118-z
|View full text |Cite
|
Sign up to set email alerts
|

A photochemical approach to anchor Au NPs on MXene as a prominent SERS substrate for ultrasensitive detection of chlorpromazine

Abstract: As a novel two-dimensional (2D) material, metal carbide (MXene) has been identified as a hotspot research topic in the field of surface-enhanced Raman spectroscopy (SERS). Herein, we report the increment of SERS activity of titanium carbide (TiC) by incorporation of gold nanoparticles (Au NPs) by a facile photoreduction process for the detection of antipsychotic drug. TiC anchored with Au NPs produce a remarkable SERS enhancement by the synergistic action of chemical and electromagnetic mechanisms. The hotspot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…For efficient interaction with probe molecules, the hotspots are created in the nanometer-scale spaces between Au NPs on the TiC surface ( Figure 11 a). The suggested MXene/Au-NPs SERS platform was used to detect chlorpromazine with a limit of detection of 3.92 × 10 −11 M and a wide linear range of 10 −1 –10 −10 M. Additionally, the enhanced TiC/Au-NP SERS effect for the 532 nm excitation shows a better prediction in the order of 109 with relative standard deviations of 13% for uniform and 8.80% for reproducibility [ 96 ]. It is possible to tailor the plasma frequencies throughout a wide spectral range, from the mid-infrared to near-infrared, by combining interband transitions and boundary effects ( Figure 11 b,c).…”
Section: Application Of Mxenes Materials For Sensorsmentioning
confidence: 99%
“…For efficient interaction with probe molecules, the hotspots are created in the nanometer-scale spaces between Au NPs on the TiC surface ( Figure 11 a). The suggested MXene/Au-NPs SERS platform was used to detect chlorpromazine with a limit of detection of 3.92 × 10 −11 M and a wide linear range of 10 −1 –10 −10 M. Additionally, the enhanced TiC/Au-NP SERS effect for the 532 nm excitation shows a better prediction in the order of 109 with relative standard deviations of 13% for uniform and 8.80% for reproducibility [ 96 ]. It is possible to tailor the plasma frequencies throughout a wide spectral range, from the mid-infrared to near-infrared, by combining interband transitions and boundary effects ( Figure 11 b,c).…”
Section: Application Of Mxenes Materials For Sensorsmentioning
confidence: 99%
“…Cheng et al showed that it is possible to monitor this drug in a concentration range of from 3.26 × 10 −9 M for CBZ in saliva [69] (see Figure 9). Barveen, Wang, and Chang proposed a different non-invasive approach to drug detection, that of detecting chlorpromazine (CPZ) in human saliva or urine [70]. This method used gold nanoparticles on TiC as the SERS substrate.…”
Section: Drugs Monitoringmentioning
confidence: 99%
“…The use of such a SERS sensor made it possible to detect DOX in undiluted blood, with a detection limit of 20 nM. Barveen, Wang, and Chang proposed a different non-invasive approach to drug detection, that of detecting chlorpromazine (CPZ) in human saliva or urine [70]. This method used gold nanoparticles on TiC as the SERS substrate.…”
Section: Drugs Monitoringmentioning
confidence: 99%
“…Ag and Au are widely adapted plasmonic materials along with their superior LSPR resonance intensity, stability, and wide wavelength range in which most of Raman emission takes place [ 9 , 11 , 13 ]. Various Ag and Au-based plasmonic platforms have been widely explored for SERS enhancement such as Ag nanorods, porous AgAu NPs, Ag/GQD, Au NPs/MXene, and so forth [ 8 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. The bimetallic hybrid NP configuration can provide extended options to alert the size- and shape-dependent LSPR [ 8 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%